Transparency and accountability in municipal health care: Wao's health programs - Guatno, Izel Marie B. (Animo Repository, 2011)
This case presents how the Wao municipality’s health programs, which were recognized as best practices, were developed and implemented in accordance to the values of transparency, accountability, and participatory leadership as espoused by its local chief executive, Mayor Elvino B. Balicao, Jr.